Local People Knowledge about Plant Trees Species Inside Tropical Forest of Tengger Ranupani - Hardyanti, Setyo Ayu; Hakim, Luchman (Biotropika: Journal of Tropical Biology, 2014)
Degradation of Â tropical forests in Indonesia is Â known more widespread. The development of Â societyactivities Â is Â known to be very fast, thus Â it Â causes Â land degradation. An Â effort Â to make ecosystemÂ reparation of the tropical forest through restoration becomes very important to be done. The success ofÂ these efforts cannot be separated from the local community factors. The purpose of this study Â is Â toÂ determine rainforest woody plant species that are recognized, and utilized Â also knowing the Â publicÂ perceptions in tropical forest restoration. The method used is quantitative ethnobotany with estimatingthe significance of the plant based on the level of popularity Â herbs known and frequently used by theÂ society. Â The data Â were analyzed using the Relative Frequency of Citations (RFC) and RelativeÂ Importance (RI). There are thirtyfive plants that are mentioned by society. Eighteen species are woodyÂ plants. The highest value of RFC from the interview are pine (Casuarina junghuhniana) that the valueÂ is Â 1. It Â is often Â used to Â fill the need Â as a building material and firewood. Â The Â smallest value of Â RFC isÂ 0.07 Â randu bacin Â (Pittosporum moluccanum). Â It Â is Â caused of lacking knowledge of Â the type Â and theÂ benefits of the plants. RI value or numbers of plants Â that are most frequently mentioned is fir that is atÂ 3.56. Â Meanwhile, Â the Â smallest Â value of Â RI Â is Â randu bacin Â (Pittosporum moluccanum) Â of 0.31. Â TheÂ societyâs perception of woody plants is Â quite well. The society Â knows the benefits of forest plants andÂ the Â forest condition today. Â The societyâs Â traditional knowledge in Â benefitting Â the Â plants Â is Â to beÂ hereditary. So that Â society Â makes Â serious efforts Â to Â help Â the activity of Â forest restoration by plantingÂ vegetation.Â Keywords: degradation, forest, restoration, trees, utilization